Transcriptome-Wide Identification of G-to-A RNA Editing in Chronic Social Defeat Stress Mouse Models - Tao, Ji; Ren, Chun-Yan; Wei, Zhi-Yuan; Zhang, Fuquan; Xu, Jinyu; Chen, Jian-Huan (Frontiers in Genetics, 2021)
Emerging evidence suggests that RNA editing is associated with stress, neurological diseases and psychiatric disorders. However, the role of G-to-A RNA editing in chronic social defeat stress (CSDS) remains to unclear. We herein identified G-to-A RNA editing and its changes in the ventral tegmental area (VTA), a key region of the brain reward system, in CSDS mouse models under emotional stress (ES) and physiological stress (PS) conditions. Our results revealed 3812 high-confidence G-to-A editing events. Among them, 56 events were significantly down-regulated while 23 significantly up-regulated in CSDS compared to controls. Moreover, divergent editing patterns were observed between CSDS mice under ES and PS conditions, with 42 and 21 events significantly up-regulated in PS and ES, respectively. Interestingly, differential RNA editing was enriched in genes with multiple editing events. Genes differentially edited in CSDS included those genetically associated with mental or neurodevelopmental disorders especially mood disorders, such as FAT atypical cadherin 1 and solute carrier family 6 member 1. Notably, changes of G-to-A RNA editing was also implicated in ionotropic glutamate receptors, well-known targets of adenosine-to-inosine RNA editing. Such results demonstrate dynamic G-to-A RNA editing changes in the brain of CSDS mouse models, underlining its role as a potential molecular mechanism of CSDS and stress-related diseases.